Effect of Fenugreek (Methi) on Cortical Thickness of the Thymus in Streptozotocin-Induced Diabetic Rats (Bangladesh Journal of Anatomy, 2009)
Objective: To find out microscopically whether Trigonella foenumgraecum (fenugreek seeds/methi seeds) has got any preventive role against the lowering of cortical thickness of the thymic lobules in diabetes mellitus. Design: An experimental study on Long Evans rats which were divided into three equal groups depending on their different shorts of dietary feeding and drug treatment. Setting: Anatomy department of IPGMR (Institute of Post Graduate Medicine and Research) at present BSMMU (Bangabandhu Sheikh Mujib Medical University) and BIRDEM (Bangladesh Institute of Research and Rehabilitation in diabetes, Endocrine & Metabolic Disorders). Subjects: Fifty eight healthy young Long Evans rats of either sex weighing 72 to 174gm aged between 50 to 60 days were used in this study. Main outcome measures: Variation of cortical thickness of the thymic lobules in different groups of rat. Result: Cortical thickness in the nondiabetic control group, which ranges from 30.17 to 36.99. and the mean was 34.83 ± 0.60. In diabetic control group the cortical thickness ranges from 17.78 to 26.46 and the mean was 21.85 ± 1 On the other hand, in the fenugreek- treated diabetic rats the cortical thickness ranges from 25.71 to 32.95 and mean cortical thickness was 30.49 ± 0.75. Conclusion: Fenugreek showed a tendency of acting against lowering of the cortical thickness of the thymic lobule of Streptozotocin-induced diabetes mellitus. However, further investigations are recommended for establishing fenugreek as a safe, useful effective agent to preserve the cortical thickness improving the diabetic condition by acting as antidiabetogenic agent. Key words: Diabetes mellitus, Differential lymphocyte count, Fenugreek, Thymus   doi: 10.3329/bja.v7i1.3017 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 37-41